The Financing Of The European Union Budget - Matthijs (1), Herman (Advances in Social Sciences Research Journal, 2018)
The European Union (E.U.) has a special system of financing its institutions. The system has been the subject of political discussion for many years. The current financing system has been in place since 1970 and was modified in 2014. But this system has come under increasing pressure as a result of the growth of the number of member states and growing economic disparity between the member states. The question of whether to rely on its own sources of finance or on contributions from its members is the subject of a separate political argument.